Analisis Faktor Penyebab Anak Berhadapan dengan Hukum dan Efektivitas Program Diversi di Indonesia - Diendha Fahira Mayliyanti; Uut Rahayuningsih; Ryo Jauhari Saputra; M. Inzaghi Wahyu Ramadhan (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
This study aims to analyze the contributing factors that lead children to come into conflict with the law and to evaluate the effectiveness of diversion programs in reducing recidivism among juvenile offenders. Using a socio-legal approach and qualitative method, data were collected through literature review, interviews with law enforcement officers and community counselors, and direct observation of diversion implementation in several regions. The findings indicate that the causes of juvenile delinquency are multifaceted, including social, economic, psychological, educational, and media-related influences. Diversion programs, when implemented holistically and based on restorative justice principles, have proven effective in reducing recidivism rates. Nevertheless, several challenges persist, such as limited understanding of restorative justice among legal practitioners, inadequate facilities, and societal stigma against children in conflict with the law. Therefore, a collaborative and continuous effort is needed to enhance the quality of diversion practices, strengthen regulations, improve infrastructure, and increase community involvement to establish a juvenile justice system that prioritizes the best interests of the child.